Systematic review and case series: flexible sigmoidoscopy identifies most cases of checkpoint inhibitor‐induced colitis. Issue 12 (29th April 2019) - Wright, Andrew P.; Piper, Marc S.; Bishu, Shrinivas; Stidham, Ryan W.
Summary: Background: Immune checkpoint inhibitors are used in the treatment of multiple advanced stage cancers but can induce immune‐mediated colitis necessitating treatment with immunosuppressive medications. Diagnostic colonoscopy is often performed but requires bowel preparation and may delay diagnosis and treatment. Sigmoidoscopy can be performed rapidly without oral bowel preparation or sedation. Aims: Characterize the colonic distribution of immune‐mediated colitis to determine the most efficient endoscopic approach. Methods: A systematic review of checkpoint inhibitor‐induced colitis case reports and series was conducted in both PubMed and Embase through 3 January 2017. A single centre retrospective chart review of patients who underwent endoscopic evaluation for diarrhoea after treatment with a checkpoint inhibitor (ipilimumab, nivolumab or pembrolizumab) between 1 January 2011 and 3 January 2017 was performed. Clinical, endoscopic and histologic data were collected. Results: A detailed systematic review resulted in 61 studies, in which 226 cases of colitis were diagnosed by lower endoscopy (125 colonoscopy, 101 sigmoidoscopy). Only four patients had isolated findings proximal to the left colon. In our centre, 31 patients had histologic features of checkpoint inhibitor‐induced colitis, for which 29 patients had complete data. The left colon was involved in all cases. Sigmoidoscopy would be sufficient to diagnose >98% of reported cases of checkpoint inhibitor‐mediated colitis diagnosed by lower endoscopy. Conclusions: Moderate to severe checkpoint inhibitor‐induced colitis involves the left colon in the majority of cases (>98%). Sigmoidoscopy should be the initial endoscopic procedure in the evaluation of this condition.